Increased active phase atrial contraction is related to marathon runner performance - Gabrielli, L.; Herrera, S.; Contreras-Briceno, F.; Vega, J.; Ocaranza, M. P.; Yanez, F.; Fernández, R.; Saavedra, R.; Sitges, M.; García, L.; Chiong, M.; Lavandero, S.; et al. (European Journal of Applied Physiology, 2018)
Purpose: Left atrial (LA) contraction is essential for left ventricular (LV) filling during exertion. We sought to evaluate the relationship of LA contraction and exercise capacity in trained athletes. Methods: Sixteen male marathon runners were recruited and allocated into two groups according to their previous training status (= or < 100 km peer week). All subjects underwent a baseline cardiopulmonary test to evaluate maximal aerobic capacity and a transthoracic echocardiography previous and immediate post-marathon. LA contractile function evaluation was accomplished by measuring the negative deformation of the post P wave strain curve (LASa). LASa change was defined as LASa pre-marathon minus LASa immediate post-marathon. Results: Mean age was 39 ± 6 years. LA volume index (39 ± 13 vs. 31 ± 5 mL/m2, p = 0.04), LV mass index (91 ± 21 vs. 73 ± 12 g/m2, p = 0.04), VO2 max (59 ± 3 vs. 50 ± 8 mL/kg/min, p = 0.036) were higher in more intensive trained group and marathon time was lower (185 ± 14 vs. 219 ± 24 min, p = 0.017). An increase in LASa after immediate post-marathon was observed in both groups, which was significantly greater in the highly trained group (18.9 ± 5.8 vs. 6.3 ± 3.5%, p < 0.003). Maximum VO2 measured previous to the marathon was inversely related to marathon time and directly correlated to LASa change (rho = 0.744, p = 0.001, rho = 0.546, p = 0.028, respectively). Conclusions: Athletes with more intensive training load have larger LV mass and LA size. An increase in LA contraction was seen post-marathon, which was significantly greater in the highly trained group. This increase in the LA contraction was related to the maximum VO2 measured previous to the marathon and to performance in a highly demanding test.